Novel Ferrocenyl-substituted Organometallics with Pyrimidine Moiety as Potent Antiprotozoal Agents: Synthesis, Characterization and in Silico Evaluation : Ferrocenyl substituted organometallics/heterocyclic compounds as potent antiprotozoal agents - Parveen, Humaira; YOUNUS WANI, MOHAMMAD; ALOTAIBI, FATIMAH A.; MUKHTAR, SAYEED; FARIDI, UZMA (Asian Journal of Chemistry, 2023)
Metallodrugs have been extensively used in modern research to design and synthesize new core drug molecules. In search of new leads in protozoal chemotherapy, we have synthesized novel ferrocene-substituted pyrimidine-based organometallic compounds and thoroughly investigated their ADMET [Absorption, distribution, metabolism, excretion and toxicity] and pharmacokinetic properties. The compounds exhibited excellent solubility potential, with favourable permeability and absorption characteristics. They demonstrated low toxicity, as indicated by clearance values and oral toxicity measurements. Molecular docking studies revealed strong interactions with the target site, surpassing the performance of reference drugs metronidazole and ornidazole. Overall, these organometallic compounds possess desirable ADMET profiles, meet Lipinski's criteria, and exhibit promising drug-likeness properties, positioning them as potential leads for the development of effective antiprotozoal agents.